The effectiveness of cardiac resynchronization therapy for patients with New York Heart Association class IV non‐ambulatory heart failure. Issue 4 (14th February 2015) - Yamashita, Soichiro; Fukuzawa, Koji; Yoshida, Akihiro; Itoh, Mitsuaki; Imamura, Kimitake; Fujiwara, Ryudo; Suzuki, Atsushi; Nakanishi, Tomoyuki; Matsumoto, Akinori; Kanda, Gaku; Kiuchi, Kunihiko; Shimane, Akira; et al.
Abstract: Background: We reviewed the effectiveness and safety of cardiac resynchronization therapy (CRT) for patients with New York Heart Association (NYHA) class IV non‐ambulatory heart failure (NAHF). Methods: From 2006 to 2011, 310 patients underwent CRT at Kobe University Hospital and Himeji Cardiovascular Center because of heart failure. Of these, 29 NAHF patients were retrospectively analyzed. The control group comprised 21 age‐ and ejection fraction‐matched patients with NAHF who did not undergo CRT from the ICU database of Kobe University Hospital. The primary endpoint was all‐cause death and hospitalization for heart failure. Response was defined as a >15% reduction in left ventricular end‐systolic volume (LVESV). Results: CRT was performed successfully without serious complications in all patients. Twenty‐three patients (79%) were discharged 19±15 days after CRT implantation, while 6 (21%) died during their hospital stay due to progressive heart failure. Compared with the control group, patients in the CRT group showed significant improvements in the primary endpoint (log‐rank p =0.04). Six patients (21%) were defined as responders and the Kaplan–Meier curve showed that responders experienced a better outcome than non‐responders (log‐rank p =0.029). LV dyssynchrony before implantation was significantly related to the occurrence of the primary endpoint ( p =0.02). Conclusions: CRT can be safely used in patients with NAHF and can improve long‐term patient outcomes, especially in treatment responders.